Model Pembiayaan Syariah Untuk Perkembangan Perkebunan Kopi di Kabupaten Bener Meriah - Ali Muamar; Jafril Khalil; Manager Nasution; Arief Safari; Riawan Amin; Aries Muftie (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2018)
This study was conducted to examine the effect of Free Cash Flow Ratio, Debt Equity Ratio (DER), Institutional Ownership, Employee Welfare and Price Earning Ratio (PER) to Divident Payout Ratio (Parliament) partially on manufacturing companies listed on Indonesia Stock Exchange period 2011-2015. In addition, to test the feasibility of regression model, the influence of Free Cash Flow Ratio, Debt Equity Ratio (DER), Institutional Ownership, Employee Welfare and Price Earning Ratio (PER) to Divident Payout Ratio (DPR) simultaneously at manufacturing company listed on Bursa Indonesia Securities period 2011-2015. The population in this study are 146 manufacturing companies that have been and still listed in Indonesia Stock Exchange period 2011-2013. The sampling technique used was purposive sampling and obtained sample of 42 companies. Data analysis technique used is by using multiple linear regression test. The results showed that Free Cash Flow Ratio, no significant effect on Divident Payout Ratio (DPR). Debt Equity Ratio (DER) has a negative and significant influence on Divident Payout Ratio (DPR), Institutional Ownership has a significant positive effect on Divident Payout Ratio (DPR), Employee Welfare and Price.